The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0066-782x2009001100010
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade cardiovascular por sexo e faixa etária em São Paulo, Brasil: 1996 a 1998 e 2003 a 2005

Abstract: SummaryBackground: Knowledge on the trends of cardiovascular mortality is important to make hypotheses on its occurrence as well as to support prevention and control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
14

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
1
5
0
14
Order By: Relevance
“…Although some studies show a decrease in CVD deaths 1,[3][4][5][6][7][8]11,[19][20][21] , possibly due to accelerated economic development, bringing with it better living conditions and less exposure to infections during the perinatal period 4 , such deaths may present themselves in a non-homogeneous manner within the population groups of a given country, as mentioned by Frank et al 22 . Reinforcing these findings, Mansur et al 19 found an increase in the risk of death due to these diseases in the less developed states of the country, which agrees with the study by Farias et al 23 , which suggests that despite a decrease in recent years, these deaths may show different patterns in the different socioeconomic groups.…”
Section: Discussionsupporting
confidence: 73%
“…Although some studies show a decrease in CVD deaths 1,[3][4][5][6][7][8]11,[19][20][21] , possibly due to accelerated economic development, bringing with it better living conditions and less exposure to infections during the perinatal period 4 , such deaths may present themselves in a non-homogeneous manner within the population groups of a given country, as mentioned by Frank et al 22 . Reinforcing these findings, Mansur et al 19 found an increase in the risk of death due to these diseases in the less developed states of the country, which agrees with the study by Farias et al 23 , which suggests that despite a decrease in recent years, these deaths may show different patterns in the different socioeconomic groups.…”
Section: Discussionsupporting
confidence: 73%
“…For example, mortality rates due to acute complications of diabetes declined between 1991 and 2010 [7]. Between 1996 and 2007, age-adjusted mortality attributable to non-communicable diseases declined by about 20 %, primarily associated with reductions in cardiovascular disease [1, 8]. However, these mortality improvements have not been equally experienced across populations’ subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…As doenças do aparelho circulatório estão cerca de 98% mais elevados do que a segunda causa mais frequente de internações entre os idosos, que é a referente às doenças do aparelho respiratório e, cerca de quase 200% a mais do que a terceira causa de internações, que é a referente a neoplasias. Farias et al (2009) inferiram que nas últimas três décadas houve uma queda na taxa de mortalidade por doenças do aparelho circulatório no Brasil, embora este fato seja uma tendência não tão somente nacional mas mundial. Entretanto, esta tendência não foi observada no DF.…”
Section: Resultsunclassified